Economic Analysis of Law on Indonesia’s Capital Market Reform after P2SK - Mardjono, Amerta; Lie, Gunardi (JURNAL USM LAW REVIEW, 2026)
Capital market legal reform through Law Number 4 of 2023 on the Development and Strengthening of the Financial Sector (the P2SK Law) represents a comprehensive effort to address structural weaknesses in Indonesia’s financial sector. However, existing scholarship remains limited in assessing the P2SK Law in an integrative manner, particularly in linking legal efficiency with the philosophical dimension of justice in capital market governance. This analytical gap raises questions as to whether the omnibus reform not only enhances market performance but also ensures fairness for all stakeholders. This study aims to analyze the implications of the P2SK Law for regulatory efficiency, transparency, and investor protection in Indonesia’s capital market. The research employs a qualitative normative legal method using the Economic Analysis of Law (EAL), Cost–Benefit Analysis (CBA), and classical legal philosophy approaches. Primary legal materials include the P2SK Law as well as regulations issued by the Financial Services Authority (OJK) and the Indonesia Stock Exchange, which are analyzed alongside legal and financial literature as secondary sources. The findings indicate that the strengthening of OJK’s authority and the enhancement of disclosure obligations under the P2SK Law contribute to lower transaction costs and improved information symmetry, which in turn causally promote greater investor confidence and deeper market liquidity. Furthermore, the simplification of the regulatory structure reduces overlapping authority and strengthens legal certainty, thereby improving capital market governance and systemic risk mitigation. From a justice perspective, the reform also expands retail investor access and accommodates digital financial innovation, aligning with the principles of corrective and distributive justice. The novelty of this study lies in its proposal of an integrative evaluation model that combines economic efficiency and moral justice in assessing capital market regulation. This contribution is not only theoretical but also practical, offering a comprehensive policy-analysis framework for evaluating the effectiveness of modern financial-sector reforms.